PENGARUH PERCEIVED VALUE MUSLIMAH MUDA TERHADAP KEPUTUSAN BERKUNJUNG DI DESTINASI HALAL PULAU LOMBOK - Baiq Nikmatul Ulya; Sulhaini Sulhaini; Baiq Handayani Rinuastuti (Master of Management, Mataram University, 2020)
This study aims to examine the effect of perceived values, including functional, emotional, social, epistemic, conditional, and Islamic values on the decision to visit halal destination of Lombok Island. The samples were 150 young Indonesian female Muslim tourist who had visited the halal destination, aged 16-30 years. The method used is quantitative research with purposive sampling technique. The result showed that from six variables, four variables, i.e. emotional, epistemic, conditional, and Islamic values have significant effect on decision to visit, while the other two, namely: functional and social values have no significant effect on decision to visit the halal destination.Keywords:Perceived value, young Muslim women, visiting decisions, halal destinations, Lombok island